Implications of increased urbanization and consumer awareness on future food supplies in Tanzania - Marivoet, Wim; Alphonce, Roselyne (International Food Policy Research Institute, 2025)
Tanzania’s food system faces increasing pressure from rapid urbanization, population growth, and shifting consumer preferences toward more nutritious and diverse diets. This study analyzes how these macro trends will affect national food supply needs by 2050 and identifies key policy entry points to ensure an efficient, sustainable, and equitable food system transformation.